A study on the effectiveness of promotion done by ATCEN Sdn Bhd / Mardiana Mokhtar - Mokhtar, Mardiana (Faculty of Business and Management, 2009)
The research explores the Effectiveness of Promotion done by ATCEN. Factors included are personal selling, public relation, sales promotion, and websites. In May until October 2009 showed the reduce number of participants who attend ATCEN programs. Due to that problem matter, researcher do the research study on the effectiveness of promotion tools done by ATCEN. Participants who completed the questionnaire must be individual who already attend any of ATCEN programs. The objectives of this study is to know the level of the effectiveness of promotion done by ATCEN, to rank the promotional tools, to examine the distribution of promotional tools towards promotion effectiveness, and to give the recommendation to the company on what are other promotional tools that they can use in time to come. In this study, the researcher used the research design of descriptive research and exploratory research. For sampling technique, researcher used Convenience Sampling in Non-Probability for this study. Researcher distributed 100 of questionnaires to be answered by self administered and by mail but manage to get 80 of them. Reliability test, frequency, and cross tabulation has been used in this study to get the data from the questionnaire. The findings showed that promotion made by ATCEN is effective and the most effective tool is Public Relation while Website is the least effective tool. The researcher also gave some recommendation to ATCEN Sdn Bhd to improve their promotion efforts to become more effective. All the data gathered from the questionnaire has been analyzed by using Statistic Package for Social Science (SPSS) version 14.0.